Kesesuaian Model Hidrograf Satuan Sintetik Studi Kasus Sub Daerah Aliran Sungai Siak Bagian Hulu - Nurhasanah Junia; Manyuk Fauzi; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Synthetic Unit Hydrograph (SUH) is the most practical and simplest method in analyzing the flow rate in an ungauged watershed. It only needs the watershed characteristic data such as the area size of watershed and the length of the river. The flow rate data used in many water resource related planning activity such as drainage, water reservoir etc.. Some of the oftenly used SUH methodes are SCS (Soil Conservation Service), Nakaysu, Snyder’s, GAMA-I etc. The concept of Unit Hydrograph with the volume control/ DRO (Direct Run Off) value closest to1mm, is used to determine a proper SUH method to be applied on watershed. In the case study of Tapung Kiri watershed, the proper SUH method to be applied is the Nakayasu’s with the α = 2, and DRO = 0,992. Nakayasu’s is also the proper SUH to be applied in the Tapung Kanan watershed, with the α = 2, and DRO = 0,992.Keyword : UH, SUH, SCS (Soil Conservation Service), Nakayasu, Snyder, DRO, Tapung River